Benthic foraminiferal oxygen isotope data (δ18O) and age models from Northwest Atlantic sediment cores forming depth transects at Blake Outer Ridge and Cape Hatteras - Jack Wharton; Martin Renoult; Geoffrey Gebbie; Lloyd D Keigwin; Thomas M Marchitto; Mark Maslin; Delia W Oppo; David J R Thornalley (PANGAEA, 2024)
This dataset is used to reconstruct the hydrography of the Northwest Atlantic during the Mid-Holocene (2-6 ka BP) and Last Glacial Maximum (19-23 ka BP). It consists of: (1) vertical δ18O profiles derived from multi-species benthic foraminiferal δ18O measurements from sediment cores in two depth transects at Cape Hatteras (~36-39°N) and Blake Outer Ridge (~30-33°N), (2) the monospecific benthic foraminiferal δ18O measurements that underpin these profiles, (3) age constraints, including new radiocarbon dates, used to determine the relative positions of the Mid-Holocene and Last Glacial Maximum in each of the sediments cores in each transect, and (4) multi-species downcore benthic δ18O measurements from four of the sediment cores in the Cape Hatteras transect.